Diseño de la documentación bajo los requisitos de la norma NTC ISO 9001: 2015 para la empresa La Casa del Hojaldre y Pastelería (2021)
Quality management systems emerged as a strategy to promote excellence and productivity in companies, giving an important twist to the approach of organizational sciences to the company. It is based on the concept of total quality, which over time evolved into what is known today as quality management. The present project suggests the design of the QMS documentation as a means to guarantee the growth, positioning and productivity of the company. It was developed in four phases that are diagnosis of the initial compliance with the NTC ISO 9001:2015, then following the parameters of chapter 4 of the standard was carried out the contextualization of the company, the identification of its stakeholders and the factors of influence on the success of this. Then the documentation of the QMS was carried out and finally the economic impact generated by the project to the company is presented, finding a cost-benefit ratio of 72%.